An analysis of the performance of the family assitance team (TPK) in reducing stunting - Septriliyana, R. Noucie; Astuti, Dwi; Setyanto, Arif Tri; Maydianasari, Lenna (Science Midwifery, 2025)
This study aims to analyze the performance of the Family Assistance Team (TPK) in efforts to reduce stunting in District B0672 (code). The study was conducted with a parallel convergent mixed methods design, namely the collection of quantitative data through descriptive analysis of secondary data from the Institution of Population Control, Family Planning, Women's Empowerment and Child Protection Service and qualitative data through Focus Group Discussions (FGDs) involving cross-sectors. The results of the study indicate that the performance of the TPK is still not optimal, with significant disparities between assistance targets and between sub-districts. Assistance for pregnant women has good coverage, while assistance for prospective brides is still very low. The main factors affecting the performance of the TPK are limited data validation, inconsistencies in information systems between agencies, and lack of human resource capacity. This study recommends the integration of cross-sector information systems, the preparation of national standard operating procedures, and strengthening the capacity of the TPK through routine training and increased interpersonal communication in order to increase the effectiveness of the stunting reduction acceleration program.